Prostratin: An Overview - Abbas Miana, Ghulam; Riaz, Muhammad; Shahzad-ul-Hussan, Syed; Zafar Paracha, Rehan; Zafar Paracha, Usman (Mini Reviews in Medicinal Chemistry, 2015)
Terpenoid class of molecules possesses a diverse therapeutic properties and potentials owing to their specific structural features. Prostratin and its derivatives are exemplified in this context to exhibit a variety of biological activities. In this review we discuss in detail the role of prostratin as potential therapeutic and underlying molecular mechanisms by which it accomplishes these activities. Prostratin [13-O-acetyl-12-deoxyphorbol] is a phorbol ester that was first isolated from Strathmore weed Pimelea prostrate, a small endemic New Zealand shrub, and characterized by Hecker in 1976. Structurally, prostratin contains four rings designated as A, B, C and D. Ring A is trans linked to the 7-membered ring B while Ring C is a 6 membered and is cis linked to the cyclopentane ring D. Chemical synthesis of this compound initiated with acidic hydrolysis of phorbol, a tigliane diterpene isolated from croton oil. Prostratin-containing extracts have been used by the Samoan healers to treat individuals with certain medical conditions such as jaundice. Importantly, these treatments are not associated with any significant side effect. Prostratin inhibits HIV-1 infections by down regulating HIV-1 cellular receptors through the activation of protein kinase C (PKC) pathway and reduces the HIV-1 latency. Unlike other phorbol esters that induce carcinogenesis by activating PKC, prostratin does not induce tumors rather has shown tumor suppressing activity. Its ability to induce lytic gene expression supports a role for phorbol-ester regulated signaling pathways in Kaposi’s sarcoma associated herpes-virus reactivation.
Keywords: Prostartin